FACTORS THAT INFLUENCE REPEAT PURCHASES: PROMOTION, PRICE, PRODUCT QUALITY, AND BRAND (LITERATURE REVIEW) - Adi Wijaya; Muinah Fadhilah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Relevant research is very important in a research or scientific article. Related research strengthens theories and phenomena about the relationship or influence between promotional variables, price, product quality, and brand on repeat purchases. This article discusses the factors that influence repeat purchases: Promotion, Price, Product Quality and Brand, literature study on consumer behavior. The purpose of writing this article is to make hypotheses about the influence between variables used in further studies. The results of this literature review are: 1) Promotion has an effect on repeat purchases, 2) Price has an effect on repeat purchases, and 3). Product quality has an effect on repeat purchases, 4) Brand has an effect on repeat purchases. The evolution of today's business world has brought this together with business people in fierce competition for consumers. For companies engaged in the culinary field, quality of service is an important thing. This variable is very important in the decision-making process Purchases for services that satisfy consumers affect repurchase transactions which ultimately increase sales. Keywords: Repurchase, Promotion, Price, Product Quality, and Brand.